No Sensory Compensation for Olfactory Memory: Differences between Blind and Sighted People - Sorokowska, Agnieszka; Karwowski, Maciej (Frontiers in Psychology, 2017)
Blindness can be a driving force behind a variety of changes in sensory systems. When vision is missing, other modalities and higher cognitive functions can become hyper-developed through a mechanism called sensory compensation. Overall, previous studies suggest that olfactory memory in blind people can be better than that of the sighted individuals. Better performance of blind individuals in other-sensory modalities was hypothesized to be a result of, among others, intense perceptual training. At the same time, if the superiority of blind people in olfactory abilities indeed results from training, their scores should not decrease with age to such an extent as among the sighted people. Here, this hypothesis was tested in a large sample of 94 blind individuals. Olfactory memory was assessed using the Test for Olfactory Memory (TOM), comprising episodic odor recognition (discriminating previously presented odors from new odors) and two forms of semantic memory (cued and free identification of odors). Regarding episodic olfactory memory, we observed an age-related decline in correct hits in blind participants, but an age-related increase in false alarms in sighted participants. Further, age moderated the between-group differences for correct hits, but the direction of the observed effect was contrary to our expectations. The difference between blind and sighted individuals younger than 40 years old was non-significant, but older sighted individuals outperformed their blind counterparts. In conclusion, we found no positive effect of visual impairment on olfactory memory. We suggest that daily perceptual training is not enough to increase olfactory memory function in blind people.